The role of local collection in financing the Solidarity and Guarantee Fund for Local Communities to Achieve Local Development in Algeria: a case study of the state of Tebessa - messai, mounira; hamma, amieur; rahal, mourad (Journal of Excellence for Economics and Management Research, 2025)
This study aims to analyze the role of local taxation in financing the Solidarity and Guarantee Fund for Local Communities for Local Development, by analyzing the evolution of tax revenues in Tébessa, determining the structure of its taxes and fees, and analyzing the reality of tax financing for the Solidarity and Guarantee Fund for Local Communities. The study results confirmed that the tax administration demonstrated control over the implementation of tax revenues. Local collection was also found to be effective in financing the fund. It was also found that the Solidarity and Guarantee Fund for Local Authorities played a significant role in driving local development through the grants granted, which were directed towards the implementation of several development projects in the state of Tébessa